(untitled) - Partridge, Elizabeth; Weston, Martha (New York, 2001)
Bo bakes a full moon cake as a surprise for his friend Annie, but the outcome is unexpected.
Keywords: Cake; Fiction; Baking; Fiction; Mice; Fiction; Early chapter